Changes in Phenolic Compounds, Anthocyanin and Antioxidant Enzymes in Different Growth Stages Basil (Ocimum basilicum L), Using Growth Regulators - S Abdekhani; M Solouki (Institue of Medicinal Plants, ACECR, 2016)
Background: Basil (Ocimum basilicum L.), is a member of a Lamiaceae family with antibacterial and antioxidant properties in essential oils which composed of phenylpropanoids. The evidence shows that plant hormones effective on the genes expression and increases the production of secondary metabolites. Objective: The aim was to determine chanes in the content of total phenols, flavonoids, anthocyanin and antioxidant of basil at different stages, using growth regulators. Methods: This research was carried out at the Biotechnology research institute of university of zabol, a factorial experiment based on randomized complete design with 3 replications. The treatments were growth regulators (with 0.1 mM/l gibberellic acid, jasmonic acid and salicylic acid and control (sprayed with distilled water without growth regulators)) and growth stages (seedling, perflowering and flowering) and harvested after 24 hours post treatments at different stages. Results: Results showed a significant effect of growth regulators and different growth stages on the content of total phenols, flavonoids, anthocyanin and antioxidant.Total phenolics, flavonoids indicate a significant increased. Generally, the maximum amounts of the content of total phenols, flavonoids was obtained in 0.1 mM jasmonic acid, gibberellic acid in compared to the control at flowering stage. factors consist of anthocyanins, ascorbate, catalase and guaiacol peroxide activity, considerably were increased by salicylic acid and gibberellic acid compared to the cotrol at flowering stage (P≤0.05). Conclusion: The phenol compounds, flavonoids, anthocyanin and antioxidant enzymes which were increased oxidative stress, resulting from the absorption of hormones, activation of antioxidant plant and the key role of PAL.